A função do trabalho do pedagogo no Centro de Referência de Assistência Social – CRAS em Santa Izabel/PA - BESSA, Leticia Moreira (2019)
The present study is a research that aims to investigate the role and, consequently, the importance of the pedagogue in the Reference Center of Social Assistance - CRAS, Santa Izabel do Pará / PA. Seeking to know the actions developed by this professional in this space. Taking into account the training and pedagogical performance, which historically has stood out for being a profession exclusively focused on the school environment, assuming positions commonly as teacher, pedagogical coordinator and school manager. Therefore, it is important to know the possibilities beyond this environment. Thus, the study assumes a qualitative approach, since it was sought to understand speech of the participant and their actions in the institution. The data collection techniques used were observation, field diary, and semi-structured interview, with the participation of a pedagogue who currently works as coordinator in CRAS of Santa Izabel do Pará. Data collected show that the work that this professional does not only occur within the area of its formation, since it has a team of professionals who work collaboratively to assist children, youth, adults and elderly people who are in a situation of social vulnerability, or who have their rights violated, being introduced to socioeducational actions developed by a multidisciplinary team, in order to exclarecer this public about their rights and duties. That is, the profile of the pedagogue as well as his / her competences are much more comprehensive than that of teaching for the classroom, becoming a profession that can exist beyond the walls of the school environment.